Why Are Branched-Chain Amino Acids Increased in Starvation and Diabetes? - Holeček, Milan (Nutrients, 2020)
Branched-chain amino acids (BCAAs; valine, leucine, and isoleucine) are increased in starvation and diabetes mellitus. However, the pathogenesis has not been explained. It has been shown that BCAA catabolism occurs mostly in muscles due to high activity of BCAA aminotransferase, which converts BCAA and α-ketoglutarate (α-KG) to branched-chain keto acids (BCKAs) and glutamate. The loss of α-KG from the citric cycle (cataplerosis) is attenuated by glutamate conversion to α-KG in alanine aminotransferase and aspartate aminotransferase reactions, in which glycolysis is the main source of amino group acceptors, pyruvate and oxaloacetate. Irreversible oxidation of BCKA by BCKA dehydrogenase is sensitive to BCKA supply, and ratios of NADH to NAD+ and acyl-CoA to CoA-SH. It is hypothesized that decreased glycolysis and increased fatty acid oxidation, characteristic features of starvation and diabetes, cause in muscles alterations resulting in increased BCAA levels. The main alterations include (i) impaired BCAA transamination due to decreased supply of amino groups acceptors (α-KG, pyruvate, and oxaloacetate) and (ii) inhibitory influence of NADH and acyl-CoAs produced in fatty acid oxidation on citric cycle and BCKA dehydrogenase. The studies supporting the hypothesis and pros and cons of elevated BCAA concentrations are discussed in the article.
Keywords: Alanine; Insulin; diabetes mellitus; Diabetes Mellitus; Insulin Resistance; Muscles; Male; inzulinová rezistence; obesity; inzulin; Obesity; alanin; větvené aminokyseliny; hladovění; mastné kyseliny; obezita; pyruváty; Amino Acids, Branched-Chain; mužské pohlaví; glucose; kyseliny ketoglutarové; Fatty Acids; Pyruvates; insulin resistance; oxidace-redukce; transaminasy; Starvation; lidé; svaly; ženské pohlaví; insulin; Humans; Ketoglutaric Acids; Glycolysis; Oxidation-Reduction; alanine; Female; Transaminases; glykolýza; pyruvate